League 3 of Indonesia Bali Zone: Shots and patterns of scoring a goal - I Wayan Artanayasa; Hendra Mashuri; Ketut Chandra Adinata Kusuma (UIR Press, 2022)
An indicator of a success football team in a match is to score more goals than its opponents. Continuous and stable victories can be achieved by applying sports science and technology, one of them in this case is analyzing team performance. The purpose of this study is to describe the pattern of shots taken and goals scored during League 3 of Indonesia Bali Zone in 2021. The research method chosen for this study is descriptive quantitative research. A total of 38 matches are observed to see the number of shots and goals scoring patterns based on time intervals (15 minutes), type of play, number of passes before shot and goal scoring, player action before shooting and goal scoring, playing zone and player position in play. The result of this study indicates that 52.9% of shots occurred in the first half and 51.8% of goals are scored in the second half. Shots (78%) and goals (77%) occurred through the open play process. 61.2% of shots and 64.7% of goal scoring come from the lowest number of passes (0-4 passes). In the central ultra-offensive zone, there are 43.7% shots and 71.2% goal scoring. Based on the playing position, the midfielder recorded the number of shots 34.5% and the striker got 39.6% in scoring goals. The findings of this study can provide information for coaches in seeing the scoring pattern of all teams playing in the Indonesia League 3 Bali Zone. Therefore, it has implications for the way the coach prepares a tactical training program that focuses on how to goal scoring. The limitation of this study is that it has not identified the part of the goal area that produces score. It is important further to examine the part of the goal area where the ball is often conceded or scored by the opponent.